Characterization and Alignment of Carbon Nanofibers under Shear Force in Microchannel. (17th March 2016) - Yang, Jinshan; Dong, Shaoming; Webster, David; Gilmore, John; Xu, Chengying
Abstract : This work presents a novel method to align CNFs by using shear forces in microchannels. Effect of two different microchannel sizes (1 mm × 0.1 mm and 1 mm × 0.2 mm) on CNFs alignment is investigated. SEM images of CNFs preform display significant alignment by both microchannels, which can be interpreted using a second-order alignment tensor and a manual angle meter. In the second-order alignment tensor description, an elongated ellipse can signify high degree of alignment in the direction of the major axis. When the microchannel size is 1 mm × 0.2 mm, the lengths of major and minor axes of the ellipse are 0.982 to 0.018. An angle meter manually shows that 85% of the CNFs are aligned in the direction between 60° and 90° when the microchannel is 1 mm × 0.2 mm. Both methods can demonstrate that better alignment of CNFs can be obtained using the 1 mm × 0.2 mm microchannel.